ANALISIS PENGENDALIAN SISTEM ENTERPRISE RESOURCE PLANNING (ERP) UNTUK MENINGKATKAN KEGIATAN PENGADAAN BARANG PADA PT KAWASAN INDUSTRI GRESIK - Suparman, Petrus (Fakultas Ekonomi Universitas Gresik, 2019)
Along with the changing times, Enterprise Resource Planning (ERP) systems are now in great demand by many company management, because it has many advantages. This study aims to determine and analyze the role of controlling Enterprise Resource Planning (ERP) systems to increase procurement activities. The type of research used is qualitative. The method used in this study is descriptive qualitative. The results of the research conducted by the researcher stated that the role of controlling the system of Enteprise Resource Planning (ERP) to increase the procurement activities of the goods was very good, but there were several things which according to the researchers must be corrected immediately (1) Adding the function of making SPK (Work Order) (2) Integrating into the financial system so that the old system of the cashter system does not need to be used againDOI 10.5281/zenodo.3629915